A novel channel assignment algorithm based on topology simplification in multi-radio wirelesss mesh networks - Leiming Xu; Yong Xiang; Meilin Shi (2006 IEEE International Performance Computing and Communications Conference, 2006)
By equipping each node with multiple radio interfaces, multi-channels can be utilized to improve performance of wireless mesh networks. How to assign wireless channels to interfaces to avoid collisions extremely while the network keeps a good topology is a key problem for multi-radio wireless mesh networks. We reexamine the general requirements of this problem and propose an algorithm to solve it effectively and efficiently. We regard it as a particular edge coloring problem, and propose a strategy of two steps: edge grouping and coloring edge groups. A heuristic algorithm is proposed to solve the coloring problem for edge groups. And, in order to obtain a good edge grouping, we combine topology simplification techniques with edge grouping so as to make this problem simplified. Some results demonstrate the effectiveness of our algorithms and simulations show that both flooding traffic and unicast traffic get substantial performance gains by channel assignment